Growth and reproductive characteristics in heifers fed endophyte-infected tall fescue and oxytetracycline - C.W. Peters; F.K. Brazle; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1993)
Heifers developed on high-endophyte, tall fescue gained half as much weight (56 vs 117 lb; P<.01) and had a lower 35-day pregnancy rate (15 vs 58%; P<.01) compared to heifers fed low endophyte, tall fescue. Based on progesterone serum concentrations and visual determination of estrus, the proportion of heifers that had attained puberty by the start of the breeding season tended (P=.11) to be greater when fed oxytetracycline (55 vs 68%).
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Tall fescue; Reproduction; Puberty; Beef heifers; Oxytetracycline